Graphene photodetectors with a bandwidth >76 GHz fabricated in a 6″ wafer process line. (27th February 2017) - Schall, Daniel; Porschatis, Caroline; Otto, Martin; Neumaier, Daniel
Abstract: In recent years, the data traffic has grown exponentially and the forecasts indicate a huge market that could be addressed by communication infrastructure and service providers. However, the processing capacity, space, and energy consumption of the available technology is a serious bottleneck for the exploitation of these markets. Chip-integrated optical communication systems hold the promise of significantly improving these issues related to the current technology. At the moment, the answer to the question which material is best suited for ultrafast chip integrated communication systems is still open. In this manuscript we report on ultrafast graphene photodetectors with a bandwidth of more than 76 GHz well suitable for communication links faster than 100 GBit s −1 per channel. We extract an upper value of 7.2 ps for the timescale in which the bolometric photoresponse in graphene is generated. The photodetectors were fabricated on 6″ silicon-on-insulator wafers in a semiconductor pilot line, demonstrating the scalable fabrication of high-performance graphene based devices.